Spycam surveillance system with motion detector - Nusaibah, Mohd Nor (2008)
Nowadays, Surveillance security system becomes the best solution to overcome more crime cases in our country and also for house intrusion problem, with the real-time monitoring it will be an effective security system. As we know, there are many types surveillance security system has today which are too expensive and difficult to use such as for Closed-circuit television (CCTV) surveillance system, with their centralized processing in compression and recording architecture together with a simple multi-monitor visualization of the raw video streams bear several drawbacks and limitations. For that reason, the Spycam Surveillance System with Motion Detector is built to perform automated capturing scene and provides immediate response to suspicious events by optimizing webcam capturing parameters. This project is focusing on developing a surveillance system with Passive Infared Detector as a motion sensor and webcam for capturing image, both of the devices become main component in cotroling the whole system. This project has utilized Visual C++ language and its component in creating the Graphical User Interface to interfacing the hardware and the computer. There also use parallel port for computer to interact to other external device. In this project it used to interface with PIR Detector. The project which has been successfully designed with the output is images from webcam and sensor to detect any movement while the camera continues to monitor the entire scene. Hopefully this project can function to adequate surveillance system for any crucial cases.